Implicit and informal professional development: what it 'looks like', how it occurs, and why we need to research it*. Issue 1 (1st January 2019) - Evans, Linda
Abstract: The landscape of professional development and learning knowledge has expanded steadily over the last few decades. Accompanying this expansion, the field's lexicon has widened, to include terms such as 'situated' learning and learning 'in situ', which incorporate recognition that professional learning and development occur as part-and-parcel of everyday working life. Most often categorised as 'informal' or 'implicit', such professional learning and development is under-researched; resonant of an iceberg whose biggest proportion lies submerged and unseen, with only its tip exposed, the bulk of professional development and learning activity remains unexamined by researchers, who tend predominantly to focus on 'explicit' professional development. Addressing issues that arise out of this lacuna of neglect, through short vignettes drawn from research interviews with education professionals, the author highlights recognition of something as 'a better way' as essential to the micro-level professional development process. Yet she also considers whether an actor's recollection of a professional learning or development incident or 'episode' precludes its being categorised as 'implicit'. She argues that, despite the methodological challenges involved in researching it, understanding how 'implicit' professional development occurs should be afforded a prominent place on its research agenda if the field is to advance and retain intellectual credibility.